Islamic Forum Application (IFA) - Amrouni, Khaled A. (2008)
Web-based Forum is a form of web application that allows users to discuss online in a very interactive manner which gives room for feedback. The Islamic forum can be considered as a modern type of education through which islamic knowledge can Be passed to the students or learners. Therefore, this project leads to develop a web-based forum application to help students to know Better about Islam. The requirements of the web-based application are identified by interviewing with Assoc. Prof. Dr. Shukri Ahmad, the executive manager of the Islamic Center; design the prototype of forum to implement the design.